Limited open access in socioecological systems: How do communities deal with environmental unpredictability?. Issue 2 (15th November 2018) - Chiaravalloti, Rafael Morais; Dyble, Mark
Abstract: Classical theory on the commons holds that rules are fundamental to sustainability. However, open access may be present in many sustainable socioecological systems. Here, we explore the interaction between environmental unpredictability and cooperation in a fishery in the Pantanal wetland, Brazil. We show that a variable annual flood pulse combined with channel blockages results in a high turnover in fishing grounds. To counter this variability, fishers openly share information about fishing areas with all community members, but are highly territorial with neighboring communities. We argue that this open access within communities but common property between communities represents a system of limited open access and, using a mathematical model, suggest that such a system is favored under conditions of moderate competition and high levels of resource unpredictability. Failing to take into account the social norms that underpin limited open access systems may undermine conservation interventions.